Ethics and the Simulation Facilitator: Taking your Professional Role Seriously. (June 2021) - de Wijse-van Heeswijk, Marieke
Background: When selecting, managing, and debriefing simulations, facilitators wishing to maintain appropriate standards, face demanding ethical challenges especially in learning contexts. Aim: This article considers why facilitators need to attend to ethical issues in facilitating simulation games. Issues examined include the influence ofcomplexity in socio-technical system simulation games, perceptions of both facilitator and participants' behaviors by including belief systems. Intervention: A multidisciplinary integrative view of ethicalfacilitation from a reflective perspective has been used in this article. Method: Literature, interviews and case descriptions were employed to examine what might constitute ethicalfacilitation . Results: A three layered framework of perspectives on ethicalfacilitation is proposed and two case study examples are used to describe its application. Further research is being conducted on facilitator tools for dealing with ethical issues. Conclusions: While ethicalfacilitation is undoubtedly complex, tangible perspectives with scientific foundations can be established and applied on the continuum of open and closed simulation games.